2021
DOI: 10.1007/s40273-021-01035-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-Illness Progression Before and After Diagnosis of Multiple Sclerosis: A Nationwide Register-Based Cohort Study in Sweden of People Newly Diagnosed with Multiple Sclerosis and a Population-Based Matched Reference Group

Abstract: Background Multiple sclerosis (MS) is a chronic disease associated with increased healthcare utilisation and productivity losses.Objective The objective of this study was to explore the progression of healthcare costs and productivity losses before and after diagnosis of MS in comparison to that of a population-based matched reference group. Methods We conducted a nationwide, Swedish register-based cohort study of working-aged people with MS diagnosed in 2010-12 (n = 1988) and population-based matched referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
2
2
Order By: Relevance
“…Our excess productivity losses of MS were larger than previous estimates from newly-diagnosed PwMS and predominately from permanent work incapacity [9]. Whereas the mean annual excess sickness absence costs around MS diagnosis were larger than observed in our prevalent cohort [9]. The excess productivity losses owing to sickness absence and disability pension reflect challenges that PwMS face to maintain work capacity and remain in or return to work.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Our excess productivity losses of MS were larger than previous estimates from newly-diagnosed PwMS and predominately from permanent work incapacity [9]. Whereas the mean annual excess sickness absence costs around MS diagnosis were larger than observed in our prevalent cohort [9]. The excess productivity losses owing to sickness absence and disability pension reflect challenges that PwMS face to maintain work capacity and remain in or return to work.…”
Section: Discussioncontrasting
confidence: 63%
“…Productivity losses increasingly outweigh the healthcare costs with worsening MS, as MS particularly affects young adults with the potential for many more years of paid work [ 7 , 66 ]. Our excess productivity losses of MS were larger than previous estimates from newly-diagnosed PwMS and predominately from permanent work incapacity [ 9 ]. Whereas the mean annual excess sickness absence costs around MS diagnosis were larger than observed in our prevalent cohort [ 9 ].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Cost-of-illness data can also be used in a creative way, for example, to identify patients at higher risk of developing MS. This is because a recent cost comparison between 1,988 MS patients and 7,981 matched persons without MS in Sweden indicated that MS patients have higher societal costs, health care costs and costs of productivity loss during the years prior to and following diagnosis, with the cost difference increasing over time ( 35 ). Although such an approach does not replace the use of diagnostic criteria, it may serve to trace MS patients at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%